MICROBIOLOGICAL CHARACTERIZATION OF A BRAZILIAN KEFIR GRAINS MILK - Gasser Baretta Balestrin, Marina; Pagliarini, Grasiele; Caliari, Vinicius; Gelinski, Jane Mary Lafayette Neves; Souza, Edson Luiz de; Soares, Fabiana Andreia S. De Martini (Anais eletrônicos do International Symposium on Science and Biotechnology, 2017)
Kefir is a product resulting from the symbiosis between lactic acid bacteria and acetic acid bacteria, presenting probiotic action, such as immune system stimulation, antimicrobial activity against pathogens, intestinal microbiota balance and antitumor action. The present study aimed to the characterization and microbiological identification population the grains to the Brazilian milk kefir. A sample of kefir produced in the Videira/Santa Catarina region was evaluated. For this, ten grams of the sample were inoculated in 30mL of distilled water with 3 grams of skimmed milk powder and incubated for 24 hours at 28ºC. The sample was diluted and plated for isolation on MRS agar, M17 agar, Mycosel agar, YM agar and SD agar. The predominant population was lactic acid bacteria (70.5%), followed by yeasts (29.5%). The former ranged from 109 to 1011 CFU / g and yeasts from 104 to 105 CFU / g. Gram staining and optical microscopy were also performed to identify the prevalence of the microbiota by bacillary cells (short and curvad long) and gram-positive cocci, which grew in association with slightly oval yeast cells. In the catalase test there was a predominance of positive catalase. The result of the presence of distinct microbial populations in kefir shows the need to better explore the microbial composition of the same.